Fifteen years of monitoring of POPs in the breast milk, Czech Republic, 1994-2009: trends and factors - Mikeš, Ondřej; Cupr, Pavel; Kohút, Lukáš; Krsková, Andrea; Cerná, Milena (Environmental science and pollution research international, 2012)
BACKGROUND, AIM AND SCOPE: The breast milk has been recommended to carry out as a monitoring tool for effectiveness evaluation of the Stockholm Convention on Persistent Organic Pollutants (POPs). Polychlorinated biphenyls (PCBs), dichlorodiphenyltrichloro-ethane (DDT) and its metabolites (DDX), hexachlorbenzene (HCB) and isomers of hexachlocyklohexane (HCHs) have been monitored in the breast milk of nursing mothers in the Czech Republic since 1994 as a part of The Environmental Health Monitoring System. Knowledge about long-term POPs distribution and accumulation in the human body is crucial to understanding uptake, degradation and subsequent effects as well as to conduct risk assessments. The main aim of this study is to evaluate 15-years long-term trends of selected POPs in human milk in the Czech Republic and to elucidate the questionnaire information about the age, parity and social habits, to the final concentrations. This effectiveness evaluation of POPs restriction is quite precisely after 15-years monitoring campaigns. MATERIALS, METHODS AND RESULTS: The human milk samples (4,753 samples) were analysed for a number of chlorinated organic chemicals including PCBs and selected chlorinated pesticides (OCPs, HCB, HCHs, DDX). The relative change of concentration per year for all chemicals was analysed. The remaining percentages of POPs in breast milk in comparison to 1994 are also expressed. Czech population half-lives of POPs in breast milk, derived from either linear or exponential models were computed. CONCLUSIONS AND PERSPECTIVES: The long-term data indicates a continuation of a decreasing trend of POPs concentrations on breast milk. Our study did not confirm lactation and parity as an important outflux resulting in the decrease in concentrations in mothers, which is in the antagonism with most of the studies. The higher BMI was associated with higher amounts of HCB and lower amounts of higher chlorinated PCBs. The results confirm the effectiveness of restrictions of POPs usage in the Czech Republic. This ongoing long-term study is very useful tool for parametric effectiveness evaluation of Stockholm Convention.
Keywords: lidé; Adult; hexachlorbenzen; Parity; parita; Hexachlorobenzene; Female; věkové faktory; hexachlorcyklohexan; Humans; Environmental Pollutants; DDT; dichlordifenyldichlorethylen; Česká republika; monitorování životního prostředí; Environmental Monitoring; mladý dospělý; Czech Republic; ženské pohlaví; Milk, Human; Young Adult; Age Factors; mateřské mléko; Dichlorodiphenyl Dichloroethylene; látky znečišťující životní prostředí; Hexachlorocyclohexane; dospělí; polychlorované bifenyly; Polychlorinated Biphenyls